ANALISIS PERBANDINGAN RISIKO BIAYA KONTRAK LUMPSUM DAN KONTRAK UNIT PRICE DENGAN METODE AHP (STUDI KASUS KONTRAKTOR DI KOTA DENPASAR) - Oka Suputra, I Gusti Ngurah; Wiranatha, Anak Agung (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009, 2009)
Two things that always emerge in business activity, including construction business, are either earning profit or suffering risk of loss, directly or indirectly. Many efforts have been done by contractors as the service provider, to avoid or to mitigate risk in order to achieve the effective result. One of these is by analyzing risk in terms of the type of project contract that is comparing between Lumpsum contract and Unit Price contract from the contractor view. The method used is Analytic Hierarchy Process (AHP). Analysis process initially started from collecting the problems and making the hierarchy structure. The hierarchy consists of three levels, that are objective (level I), criterion (level II), and alternatif (level III). Based on the hierarchy then followed by composing a series of questionnaires. Data was collected from questionnaires that were distributed to 20 respondents of contractors in Denpasar Regency. The data were then analyzed by creating and comparing matrices, scaling priority weight of level II and III, and checking the consistency as well. The analysis result shows that priority value of lump sum contract is 81,70% and the value of unit price contract is 18,30%. It means that lump sum contract has higher risk of loss compare to unit price contract.
Keywords: risk, contract, Analytic Hierarchy Process (AHP).